Experimental investigation on volumetric strain accumulation of saturated marine sands subjected to wave-induced complex cyclic loading - Wu, Yanshen; Zhu, Zhirui; Wu, Qi; Xu, Gaofeng; Chen, Guoxin (Frontiers in Earth Science, 2026)
The dilatancy of marine sands highly depends on the complex cyclic stress paths caused by waves. A series of the axial-torsional coupling cyclic loading tests are performed on the saturated marine sands under isotropically consolidated condition by using the Hollow Cyclic Apparatus (HCA). The dilatant behavior of saturated sands is investigated under complex stress paths, as well as the correspondent mathematical model. The results are summarized as follows: The volumetric strain of sands is composed of a completely reversible component and an irreversible component. The cyclic stress path has significant effects on the development of volumetric strain. The equivalent cyclic stress ratio (ESR), which is defined as the ratio of the mean value of the maximum stress in a loading cycle to the initial effective confining pressure can be used as an index to quantitatively characterize the cyclic stress paths of the soil sample under wave-induced axial-torsional loading. The accumulated volumetric strain (εvd,ir) increment may be uniquely correlated to the applied ESR, which accumulates linearly with the increase of ESR. By introducing ESR, A stress-dependent normalized εvd,ir incremental model of the saturated sands under complex cyclic loading was presented. Retrospective simulation of a laboratory test using the proposed model shows good agreement, calibrating the reliability of the model. However, the modified Byrne model significantly underestimates the volumetric strain accumulation of the saturated marine sands under the axial-torsional coupling cyclic loading, which was built on the data of direct shear tests. The proposed model provides a practical tool for estimating the long-term accumulation of volumetric strain and consequent settlement in offshore foundation soils, such as those supporting wind turbines or pipelines, under the action of complex storm-wave loading.